VALIDITY OF MOBILE LEARNING-BASED LEARNING MEDIA ON SMARTPHONES HYDROCARBON MATERIALS - Jintan, Putri Ranik; Pardi, Hilfi; Fitriani, Rita (SPIN JURNAL KIMIA & PENDIDIKAN KIMIA, 2023)
This research was aimed to develop learning media, as well test the level validity of mobile learning based learning media on hydrocarbon material smartphones. This development research uses the smart apps creator software and the canva application. This research used the Research and Development (R&D), with the ADDIE development model. In this study focused on the media development stage/development stage. The research subjects were one chemistry teacher and 35 students in class XI MIPA SMA Negeri 4 Tanjungpinang. The results of media validation in the development of mobile learning based learning media on smartphones on hydrocarbon material obtained a result of 68.75% with valid criteria and the results of material validation obtained a value of 89.28 % with very valid criteria. Based on the research that has been done, it can be concluded that mobile learning based learning media on hydrocarbon material smartphones is valid so it is suitable for use in chemistry learning.